Can Augmented Reality Support Science Learning in the Era of Education 5.0?: A Review - Arie Wahyu Prananta (Jurnal Penelitian Pendidikan IPA, 2025)
Many teachers find it difficult to create science learning media and do not have enough time to develop them. Many complain about the difficulty in understanding material involving formulas and unfamiliar terms. These abstract concepts in science are what make students tend to stay away from learning. The purpose of this study is to explain Can Augmented reality support science learning in the era of education 5.0?; Review. This review was conducted based on the review method. The results of this study explain about science literacy in society (learning in schools and universities) 5.0, namely the society 5.0 era is present as an answer to the problem of justice and equality of shared prosperity; advantages and disadvantages of augmented reality in science learning: the advantages of AR are: More interactive; Effective in use; Can be widely distributed on various media; Simple object modeling because it only displays a few objects; Manufacturers do not spend too much money;. Easy-to-use AR media also has disadvantages, namely: Sensitive to changes in perspective. There are not many manufacturers; Requires a lot of memory on the installed device; Requires AR-enabled hardware.